Nyi Ageng Serang Tokoh Wanita Pejuang Bangsa - Soelistijanto, R. (DIMENSI, 2013)
Nyi Ageng Serang is a women noble. She lived and married and then she fought against The Netherland Indies at Java together with Diponegoro Prince. She was a good leader. The Netherland Indies were afraid to met Nyi Ageng Serangâs troops. She fought against Netherland Indies until the war is over. There are many wisdom from the story of Nyi Ageng Serang. Indonesian young generations can learn from Nyi Ageng Serang that sheâs a good woman, a good wife, a good mother and a good citizen. Nyi Ageng Serang was nationalist patriot. She served for Indonesian motherland. This is a character education from the history of Nyi Ageng Serang. Nyi Ageng Serang is the Indonesian Women Figure.Â Key word : nyi ageng serang, women figure